The Pedagogy of Delayed Divine Response: A Sufi Perspective on Spiritual Education in the Seventh Wisdom of Al-Hikam - Musthofa Musthofa (Journal of Educational Management Research, 2026)
The phenomenon of delayed divine response to prayer often generates disappointment, anxiety, and spiritual uncertainty among contemporary Muslims, particularly within a culture that emphasizes instant gratification and immediate outcomes. This study aims to analyze the concept of delayed divine response to prayer in the Seventh Wisdom of Al-Hikam by Ibn ‘Atha’illah al-Sakandari and to examine its relevance to contemporary Muslim spirituality. Employing a qualitative approach with a library research design, the study utilized Al-Hikam as the primary source, supported by the Qur’an, Hadith, classical Sufi literature, and contemporary scholarly works. Data were collected through documentary research and analyzed using data condensation, data display, and conclusion verification. The findings reveal that delayed divine response should not be interpreted as divine rejection but as a form of spiritual pedagogy (tarbiyah rūḥiyyah) that cultivates patience (sabr), contentment (riḍā), and trust in God (tawakkul). This process strengthens spiritual awareness, psychological resilience, and religious commitment. The study concludes that delayed divine response functions as a transformative mechanism of spiritual growth. Theoretically, it contributes to Islamic spiritual education and Sufi studies by integrating classical Sufi teachings with contemporary perspectives on spirituality, resilience, and religious coping.